Corporate Tax Aggressiveness and Insider Trading. (2nd December 2018) - Chung, Sung Gon; Goh, Beng Wee; Lee, Jimmy; Shevlin, Terry
ABSTRACT: We examine the association between corporate tax aggressiveness and the profitability of insider trading under the assumption that insider trading profits reflect managerial opportunism. We document that insider purchase profitability, but not sales profitability, is significantly higher on average in more tax aggressive firms. We also find that the positive association between tax aggressiveness and insider purchase profitability is attenuated for firms with more effective monitoring and is accentuated for firms with a more opaque information environment. In addition, we provide empirical evidence that tax aggressiveness is significantly associated with greater insider sales volume in the fiscal year prior to a stock price crash. Finally, we find that the association between tax aggressiveness and insider purchase profitability weakens after the introduction of FIN 48, consistent with the increased transparency of tax positions under the new disclosure requirement reducing insiders' information advantage and hence their ability to profit from insider trading. To the extent that insider trading profits reflect managerial opportunism, our results are consistent with managers exploiting the opacity arising from tax aggressive activities to extract rent from shareholders, particularly those shareholders who sold their shares to the managers. Our findings are particularly important in light of the number of studies relying on the agency view of tax avoidance to develop arguments or to draw inferences. RÉSUMÉ: Audace des positions fiscales des sociétés et opérations d'initiés Les auteurs étudient le lien entre l'audace des positions fiscales des sociétés et la rentabilité des opérations d'initiés, en posant l'hypothèse que les profits engendrés par les opérations d'initiés reflètent l'opportunisme des dirigeants. Les données qu'ils recueillent révèlent que la rentabilité des achats d'initiés, contrairement à celle des ventes d'initiés, est, en moyenne, sensiblement supérieure dans le cas des sociétés dont les positions fiscales sont plus audacieuses. Les auteurs constatent également que le lien positif entre l'audace des positions fiscales et la rentabilité des achats d'initiés s'atténue chez les sociétés qui exercent une surveillance plus efficace et s'accentue chez celles dont l'environnement d'information est plus opaque. Ils recueillent, au surplus, des données empiriques attestant que l'audace des positions fiscales affiche un lien significatif avec un volume de ventes d'initiés plus élevé au cours de l'exercice précédant un effondrement du cours des actions. Enfin, les auteurs observent que le lien entre l'audace des positions fiscales et la rentabilité des achats d'initiés s'affaiblit après la publication de la FIN 48, du fait que la plus grande transparence des positions fiscales exigée par les nouvelles obligations d'information réduisent l'avantage dont bénéficient les initiés au chapitre de l'information et, partant, la possibilité qu'ils ont de tirer profit d'opérations d'initiés. Dans la mesure où les profits engendrés par les opérations d'initiés reflètent l'opportunisme des dirigeants, les résultats de l'étude confirment que ces derniers exploitent l'opacité caractérisant l'audace des mesures fiscales pour s'approprier une rente sur le compte des actionnaires, en particulier ceux qui leur cèdent leurs actions. Les résultats de l'étude sont particulièrement pertinents si l'on tient compte du nombre d'études dont les auteurs envisagent l'évitement fiscal sous l'angle de la délégation pour élaborer une argumentation ou formuler des conclusions.